UNJUK PERFORMA METODE INFORMATION EXTRACTION : LINGUISTIK PADA DOMAIN PARIWISATA - Moechtar, Fahmi Lutfiansyah; Kuntarto, Guson (Journal of BUSINESS INFORMATION SYSTEM, 2016)
The Increasing growth of information on the Internet requires ontology for always up-to-date. Ontology is a concept of domain that represented by classes, relationships, properties and instances. One way to keep ontology up-to-date is by populating the ontology. The most important aspect of the ontology population process is the information from the web (semi-structure) that will be added to ontology. The process of adding instance or ontology population has shift  from manual to automatic process. With the condition of ontology population process in Indonesia that still manual, especially in Bali tourism domain, this research focus on shows performance of automatic extraction engine methods using linguistic methods on the Bali tourism domain. In order to measure relevancy of linguistic method result the precision, recall and f-measure value was used. The result shows that the linguistic method gives the relevant results with highest score at 0.61. This score is limited with the definition of the term based on the DWIPA ontology. Keywords: Ontology population, extraction engine, linguistic method, Part of Speech